Controlling the Bandwidth of Terahertz Low‐Scattering Metasurfaces. Issue 11 (11th July 2016) - Zhao, Jie; Cheng, Qiang; Wang, Xin Ke; Yuan, Min Jie; Zhou, Xiao; Fu, Xiao Jian; Qi, Mei Qing; Liu, Shuo; Chen, Hai Bin; Zhang, Yan; Cui, Tie Jun
Abstract : Low‐scattering metasurfaces in the terahertz region can benefit a number of applications such as imaging, radar, and novel light sources. Such metasurfaces can efficiently suppress specular reflection and diffuse the energy that comes back without preferred direction. However, the accurate bandwidth control of low‐scattering metasurfaces is still a main issue to be investigated. To solve the problem, here a new strategy to realize the low‐scattering metasurfaces with desired bandwidths is proposed. Different from the earlier work, the current design is carried out within a broad spectrum instead of at a single frequency, giving rise to the arbitrarily desired bandwidth. Three basic elements are proposed to construct the new metasurface, and the diffuse reflection feature can be attributed to their destructive interferences with the change of operating frequency. The intrinsic loss of the meta‐atoms is also taken into account to make the theoretical model more accurate in the practical design. Excellent scattering‐suppression features are observed in the predefined frequency bands in both simulated and experimental results, which have very good agreements with the theoretical predictions. Abstract : A new strategy to realize the low‐scattering metasurfaces with desired bandwidths is proposed. The whole metasurface is divided into several rectangular sections with unequal sizes, which are randomly occupied by three kinds of elements with different reflection phases. The diffuse reflection feature of the device can be attributed to the destructive interferences of these elements with the change of operating frequency. Excellent scattering‐suppression features are observed in the predefined frequency bands.